The impact of pain on depression among middle-aged and older adult individuals in China: the chain mediation effect of self-rated health and life satisfaction - Juju Huang; Yifan Gui; Keke Wang (Frontiers in Public Health)
BackgroundThis research seeks to explore the association between pain and depression in middle-aged and older adult populations, with a particular focus on the mediating roles of self-rated health and life satisfaction within this framework.MethodsThe study employed data from the 2020 China Health and Retirement Longitudinal Study. Utilizing linear regression modeling, we examined the primary determinants influencing depressive symptoms in the target demographic. Throughout the investigation, we applied Pearson correlation analysis to clarify the relationships among pain, depression, self-rated health, and life satisfaction. Additionally, the PROCESS 3.4 macro was utilized to evaluate the potential mediating effects of self-rated health and life satisfaction on the connection between pain and depression.ResultA significant negative correlation was observed between pain and both self-rated health and life satisfaction (r = −0.381, p < 0.01; r = −0.158, p < 0.01), while a notable positive correlation with depression was identified (r = 0.356, p < 0.01). Self-rated health exhibited a positive correlation with life satisfaction (r = 0.265, p < 0.01) and a negative correlation with depression (r = −0.399, p < 0.01). Furthermore, life satisfaction was negatively correlated with depression (r = −0.359, p < 0.01). Additional analyses suggest that self-rated health and life satisfaction act as significant mediators in the relationship between pain and depression. The mediation analysis revealed that the direct effect of pain, self-reported health, life satisfaction, and depression on the outcome was 62.13%, while the indirect effect accounted for 37.87%.ConclusionThe findings of this study contribute to a deeper understanding of the dynamics between pain and depression, providing essential insights for addressing depression in the middle-aged and older adult demographic.